Understanding Fetal Alcohol Spectrum Disorder (FASD) through the Stories of Nyoongar Families and how can this Inform Policy and Service Delivery - Williams, Robyn Deanne (Curtin University, 2018)
This is the first study to explore Fetal Alcohol Spectrum Disorder (FASD) in the south west region, Western Australia. The study included a mixed methods approach of qualitative and quantitative and Indigenous Standpoint theory. The project recorded the stories of families caring for Aboriginal children with FASD and explored the level of awareness of FASD amongst the Aboriginal community. The results support the baseline international evidence for families raising children with FASD.